2021
DOI: 10.1126/sciimmunol.abm3131
|View full text |Cite
|
Sign up to set email alerts
|

Immune memory from SARS-CoV-2 infection in hamsters provides variant-independent protection but still allows virus transmission

Abstract: SARS-CoV-2 has caused significant morbidity and mortality across the globe. As the virus spreads, new variants are arising that show enhanced capacity to bypass pre-existing immunity. To understand the memory response to SARS-CoV-2, here we monitored SARS-CoV-2-specific T and B cells in a longitudinal study of infected and recovered golden hamsters. We demonstrated that engagement of the innate immune system following SARS-CoV-2 infection was delayed but was followed by a pronounced adaptive response. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
52
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 71 publications
8
52
1
Order By: Relevance
“…To explore whether this proinflammatory signal was present in additional anatomical regions linked to the olfactory bulb, olfactory epithelium was harvested from hamsters infected with SARS-CoV-2, IAV, or PBS (mock) at 30dpi as this tissue has been demonstrated to harbor infectious virus (Hoagland et al ., 2021; Horiuchi et al, 2021). Ontological analyses of mRNA-Seq data demonstrated that, similar to the olfactory bulbs, the olfactory epithelium of SARS-CoV-2-infected hamsters uniquely showed upregulated signatures for IFN-I and IFN-II (Figure 5J and S6D).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To explore whether this proinflammatory signal was present in additional anatomical regions linked to the olfactory bulb, olfactory epithelium was harvested from hamsters infected with SARS-CoV-2, IAV, or PBS (mock) at 30dpi as this tissue has been demonstrated to harbor infectious virus (Hoagland et al ., 2021; Horiuchi et al, 2021). Ontological analyses of mRNA-Seq data demonstrated that, similar to the olfactory bulbs, the olfactory epithelium of SARS-CoV-2-infected hamsters uniquely showed upregulated signatures for IFN-I and IFN-II (Figure 5J and S6D).…”
Section: Resultsmentioning
confidence: 99%
“…At 31dpi, the olfactory bulb of IAV-infected hamsters returned to a baseline transcriptional state while the same region of SARS-CoV-2-infected hamsters appeared to be in the midst of an ongoing infection characterized by microglial activation and a robust IFN-I and chemokine response. This was especially surprising given that we were unable to detect presence of viral RNA in either the olfactory bulb or lungs at this time point and, demonstrated previously, we know that hamsters generate a strong anti-S antibody response as early as seven days post infection (Hoagland et al ., 2021; Horiuchi et al ., 2021). Immunohistochemistry of MX1 corroborated our transcriptional findings and showed localization of this persistent IFN-I response to the glomerular regions of the olfactory bulbs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, T cells likely play a significant role when SARS-CoV-2 infection does not resolve quickly, such as during moderate and severe COVID-19. T cells have been implicated in control of SARS-CoV-2 in other susceptible animal models, like the human ACE2 expressing mouse lines and Syrian hamsters [78][79][80] . Furthermore, nucleocapsid specific CD8 T cells are correlated with less severe disease in patients 20 .…”
Section: Discussionmentioning
confidence: 99%
“…We did not investigate vaccine-induced T-cell responses, which may play critical roles in protection against severe COVID-19, particularly in the context of variants [43][44][45][46][47][48][49][50] . Furthermore, our assays tested only the ancestral SARS-CoV-2 strain (Wuhan or USA-WA1/2020); assessments of SARS-CoV-2 variants including Omicron are in progress.…”
Section: Discussionmentioning
confidence: 99%